2016
DOI: 10.1038/cgt.2016.19
|View full text |Cite
|
Sign up to set email alerts
|

Tumor-associated GM-CSF overexpression induces immunoinhibitory molecules via STAT3 in myeloid-suppressor cells infiltrating liver metastases

Abstract: Assumptions that liver immune cells and immunosuppressive pathways are similar to their counterparts in other spaces have led to gaps in our understanding of intrahepatic neoplasm aggressiveness. Myeloid-derived suppressor cells (MDSCs) are potent inhibitors of antitumor immunity and pose a major obstacle to solid tumor treatment. Liver MDSCs (L-MDSCs) associated with liver metastases (LM) are particularly problematic by contributing to intrahepatic immunosuppression that promotes tumor progression. L-MDSCs ha… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1
1
1

Citation Types

1
75
1

Year Published

2017
2017
2024
2024

Publication Types

Select...
6
1
1

Relationship

0
8

Authors

Journals

citations
Cited by 95 publications
(77 citation statements)
references
References 44 publications
1
75
1
Order By: Relevance
“…Galiellalactone inhibited IDO expression in monocytes, suggesting that galiellalactone may prevent immunosuppressive activities. It has previously been shown that IDO is upregulated by IL6 and GM‐CSF in MDSCs via activation of STAT3 and that STAT3 inhibition decreased this immunosuppressive activity of MDSCs . Arginase‐1 expression and activity in monocytes and MDSCs varies considerably between individuals, which may explain why we did not find a consistent effect on arginase‐1 expression in this study.…”
Section: Discussioncontrasting
confidence: 68%
“…Galiellalactone inhibited IDO expression in monocytes, suggesting that galiellalactone may prevent immunosuppressive activities. It has previously been shown that IDO is upregulated by IL6 and GM‐CSF in MDSCs via activation of STAT3 and that STAT3 inhibition decreased this immunosuppressive activity of MDSCs . Arginase‐1 expression and activity in monocytes and MDSCs varies considerably between individuals, which may explain why we did not find a consistent effect on arginase‐1 expression in this study.…”
Section: Discussioncontrasting
confidence: 68%
“…Previous studies have described factors spontaneously secreted by tumor cells that led to TNF-α production by TAM [36, 37]. These factors were also reported to stimulate macrophages to produce TNF-α in a TLR2-dependent manner.…”
Section: Resultsmentioning
confidence: 97%
“…It is possible that in GM-CSF might also come from tumor cells and other cell types in vivo. Interestingly, a recent study showed that GM-CSF secreted from tumor cells could promote PD-L1 expression in liver myeloidderived suppressor cells through Janus-activated kinase 2 (JAK2)-mediated activation of signal transducer and activator of transcription 3 (STAT3), which was able to bind to PD-L1 promoter and enhance its transcription (Thorn et al, 2016). Thus, endogenous GM-CSF from tumor cells could promote PD-L1 expression via the GM-CSF/JAK/STAT3 axis.…”
Section: Discussionmentioning
confidence: 99%